PO141 Audit of the first line oral disease modifying treatments in greater manchester. (1st December 2017) - Mihalova, Tatiana; Jackson, Fran; Lusher, William; Pace, Adrian; Sharaf, Naz; Rog, David; Talbot, Paul
Abstract : In 2014, teriflunomide and dimethyl fumarate were approved by NHS regulators as first-line oral treatments for multiple sclerosis in England. We audited the safety, tolerability and treatment retention rates of the first line oral DMTs in Greater Manchester. Case notes of MS patients treated with first line oral DMTs were analysed for drug discontinuation reason, blood monitoring compliance and drug related side effects within the first 12 months of treatment. Of 39 patients, treated with teriflunomide, 89% were still on treatment at 12 months and reported very few side effects. 5% withdrew from treatment due to non-adherence with blood test monitoring, 3% due to lack of efficacy and 3% due to side effects. 273 patients treated with dimethyl fumarate, had a retention rate of 75% after 12 months. 12% discontinued treatment due to gastrointestinal side effects and 3% due to fatigue, headache and depression. Occasionally patients reported appetite/weight changes and altered hair appearances. 6% of patients were non-adherent with blood test monitoring. Lymphocyte drop below 0.5 for more than 3 months occurred in 2%, hence treatment was discontinued. Patient retention rate was better with teriflunomide than with dimethyl fumarate. Teriflunomide blood monitoring carries a significant administrative burden but it seems to be well tolerated in our cohort.